Interpreting patients as a means of clinical practice: introducing nursing hermeneutics - Charalambous, Andreas (My University, 2010)
Background: The increased reference to hermeneutics from nursing scientists, researchers and academics has emphasized that interpretation has traditionally been a fundamental part of nursing practice. In nursing research a propensity for acquiring knowledge and understanding by using, multiple modalities has been demonstrated. In recent years, the use of hermeneutic phenomenology, has featured amongst thesemodalities. Hermeneutic phenomenology is an inquiry arm of, philosophical hermeneutics. Objectives: To explore the hypotheses that the patient can be considered as ‘‘text’’ and as such to be, interpreted in order to gain information for decision-making in clinical practice. Design: A qualitative approach (hermeneutic phenomenological) to nursing clinical practice. Settings: The clinical case of a patient suffering from cancer is described in the paper who was treated, in an Oncology Centre in Cyprus. Methods: A hermeneutical model of clinical decision-making in nursing is implemented in practice. The, model was initially used in medical practice; however it finds applications to nursing as well. According, to the model, a patient is perceived as a literary text whichmay be interpreted on four levels: (1) the, literal facts of the patient’s body and the literal story told by the patient, (2) the nursing diagnostic, meaning of the literal data, (3) the praxis (the nursing interventions) emanating from the nursing, diagnosis, and (4) the change effected by the clinical encounter in both the patient’s and nurse’s lifeworlds. Results: Nursing interventions were successfully informed by the interpretation process.
Keywords: Breast--Cancer; Nursing diagnosis; Hermeneutics; Physician practice patterns; Nursing